MODIFIKASI DAN UJI PERFORMANSI MESIN PENCACAH LIMBAH ORGANIK DAN ANORGANIK - Fakhrul Irfan Khalil; Agriananta Fahmi Hidayat; Surya Abdul Muttalib; Ida Ayu Widhiantari; Wahyudi Zulfikar (AGROINTEK, 2021)
Garbage is still an interesting issue as research material. starting from the problem of waste being a source of environmental damage and pollution to the use of waste as a resource of economic value. Based on Law No. 18/2008 on waste management, namely waste management which aims to improve public health and environmental quality and make waste a resource. One of the efforts to manage waste into something more valuable is the process of reducing the size. We need a multipurpose trash chopper that can be operated easily and affordable by the public. This research was conducted using an experimental method to test the performance of the modified waste chopper. The main modification is done to the chopping blade using a shaft with a diameter of 2.5 cm, a blade length of 10 cm with a thickness of 0.8 cm and an angle of 70o. The blade in the process chamber consists of two parts, namely the static and dynamic blades. After the testing process, the machine can be used to chop organic or inorganic waste quite well. From several experiments conducted, the effectiveness value of the chopping machine reached 95%.